2006
DOI: 10.1111/j.1365-3059.2006.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Movement of aphid-transmitted Sugarcane yellow leaf virus (ScYLV) within and between sugarcane plants

Abstract: Sugarcane yellow leaf virus (ScYLV) is distributed worldwide and has been shown to be the cause of the disease sugarcane yellow leaf syndrome (YLS). This study was an investigation of the transmission and spread of ScYLV in Hawaii. Several aphids are known to transmit the virus, but investigation of infestation and transmission efficiency showed Melanaphis sacchari to be the only vector important for field spread of the disease. The initial multiplication of ScYLV in a virus-free plant occurred exclusively in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…These cultivars were thought to be resistant to the virus (Schenck and Lehrer 2000). Lehrer and Komor (2007) reported similar results in a detailed study on YL-symptom development and SCYLV-presence over the growing season and they also found that some plants with YL symptoms tested negative for SCYLV by TBIA. They concluded that there was no close correlation between SCYLV and YL symptoms.…”
Section: Sugarcane Yellow Leaf Virus (Scylv) Is a Polerovirussupporting
confidence: 61%
See 1 more Smart Citation
“…These cultivars were thought to be resistant to the virus (Schenck and Lehrer 2000). Lehrer and Komor (2007) reported similar results in a detailed study on YL-symptom development and SCYLV-presence over the growing season and they also found that some plants with YL symptoms tested negative for SCYLV by TBIA. They concluded that there was no close correlation between SCYLV and YL symptoms.…”
Section: Sugarcane Yellow Leaf Virus (Scylv) Is a Polerovirussupporting
confidence: 61%
“…Like others in this group, SCYLV is phloem-limited (Vega et al 1997;Schenck et al 1997;Lehrer et al 2007). Symptoms in sugarcane include yellowing of the leaf midribs, short terminal internodes, reduced biomass and reduced plant vigour (Grisham et al 2002;Rassaby et al 2003).…”
Section: Sugarcane Yellow Leaf Virus (Scylv) Is a Polerovirusmentioning
confidence: 90%
“…An infection of plants after the time when the plantation was closed is very unlikely because a distance of only 100 m was already sufficient to prevent infestation from infected cane for at least 1 year (Lehrer et al 2007) and a distance of several km was not bridged by viruliferous aphids for 30 years (Fig. 4).…”
Section: Discussionmentioning
confidence: 97%
“…The aphid vector Melanaphis sacchari, which is present throughout Hawaii, will have disseminated the virus among the plants in the breeding station, infecting the cultivar collection and the newly-bred clones. Although the speed of infection propagation from plant to plant is only a few metres per year (Lehrer et al 2007, Fig. 4), it is sufficiently fast to infect susceptible varieties within a few years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation